2019
DOI: 10.3389/fpsyg.2019.02228
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Expatriates’ Cross-Cultural Adjustment on Work Stress and Job Involvement in the High-Tech Industry

Abstract: The personal traits of expatriates influence their work performance in a subsidiary. Nevertheless, organizations tend to hire candidates who are suitable from the technological dimension but ignore personal and family factors. Expatriates might not be familiar with a foreign place, and most organizations do not provide the so-called cultural adjustment training. The selected expatriates often accept the job without knowing the future prospects of their career, which can result in individual and family turmoil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 19 publications
5
156
0
2
Order By: Relevance
“…Relationship orientation was measured according to Yang's illustration [49] by 4 items (e.g., "if someone sent information to me, I will send another information to him or her later"; а = 0.74). Participants answered on a Likert-type format ranging from 1 (strongly agree) to 4 (strongly disagree).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship orientation was measured according to Yang's illustration [49] by 4 items (e.g., "if someone sent information to me, I will send another information to him or her later"; а = 0.74). Participants answered on a Likert-type format ranging from 1 (strongly agree) to 4 (strongly disagree).…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, the authority orientation, is mainly manifested in the individual's sensitivity to and worship of authority, and the natural tendency to trust in authority. Fourth, the orientation of others refers to the psychological and behavioral susceptibility to others, trying to be consistent with others, hoping to leave a good impression with others [49]. It has been found that the most common motive for sharing health information was the desire to help others [26].…”
Section: Social Orientation and Health Information Sharing Behaviormentioning
confidence: 99%
“…For entrepreneurs who emphasize internal preferences, the matching of interests and needs in their work is vital. As a result, for entrepreneurs who are more sensitive in the perception of work value and significance, the deviant innovation is the realization of their own work value, the value embodiment of work preference, and the pursuit of company interests ( Chen, 2019 ; Shen and Ho, 2020 ). Moreover, for entrepreneurs who focus on interpersonal harmony and a harmonious working atmosphere in their work, and those who expect equal communication between superiors and subordinates, will be more inclined to innovation privacy in the embodiment of deviant innovation behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Venture capital provides fund support for R&D at the stage of technology innovation input. Venture capital can hold a certain percentage of shares, participate in the supervision and governance of the enterprise, and effectively promote the continuous development of technological innovation of the enterprise (Obschonka et al, 2018;Chen, 2019;Yu et al, 2019). This paper is to explore the impact of entrepreneurial psychological capital and capital heterogeneity on venture capital behavior, and further, analyze the effect of venture capital on the innovation activities of enterprises.…”
Section: Discussionmentioning
confidence: 99%